Measurement of the lifetime of the Bc± meson in the semileptonic decay channel - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (American Physical Society (APS), 2009)
Using approximately 1.3fb-1 of data collected by the D0 detector between 2002 and 2006, we measure the lifetime of the Bc± meson in the Bc±→J/ψμ±+X final state. A simultaneous unbinned likelihood fit to the J/ψ+μ invariant mass and lifetime distributions yields a signal of 881±80(stat) candidates and a lifetime measurement of τ(Bc±)=0.448-0.036+0.038(stat)±0.032(syst)ps. © 2009 The American Physical Society.